Transforming Lexical Learning: VARK Strategies and the Role of Wayground Platform in English Language Teaching - Jafar Sodiq; Theresia Cicik Sophia Budiman; Ajeng Setyorini (Universitas PGRI Semarang, 2026)
This article explores the transformative potential of VARK (Visual, Aural, Read/Write, Kinesthetic) strategies and the digital platform Wayground in enhancing lexical learning in English language teaching. It discusses the role of Wayground platform by using the VARK strategies and to know students’ perception in using Wayground platform in Lexical Studies course in English Education Study Program. The design of this study is qualitative descriptive by exploring the role of Wayground platform integrating with VARK learning style in Lexical Studies course in English Education Study Program. The results of this study show that the VARK strategies can be beneficial to be implemented in Lexical Studies course by applying the Wayground platform. Seven themes are elaborated based on the students’ perception of the role of Wayground platform integrated with the VARK learning style in Lexical Studies course. The study synthesizes current research to establish a framework for educators on the effective implementation of these strategies in the classroom.